Recent Advances in Design and Decision Support Systems in Architecture and Urban Planning 2004
DOI: 10.1007/1-4020-2409-6_19
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Design Learning with Design Puzzles

Abstract: Abstract:The design process is a puzzle-solving process. Two groups of researches that share many similarities with Puzzle-solving design process are the process of game-playing and playful learning. The main argument is using the "playing" characteristics to amplify and explore the learning process, furthermore the design process. In addition, puzzles imply playful exploration that utilizes the characteristics of "playing a game" as "solving a puzzle". Puzzle making and puzzle solving provides an incremental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Beta waves appear when performing high degree cognitive functions such as during normal waking and concentration. Puzzle tasks, a medum which is frequently used as auxiliary materials for learning, require judgement of spatial relationships and logical thinking 20 , 21 , 22 ) , and research has shown that the frontal area is more activated 10 ) during puzzle performance. During puzzle task performance in this study there was activation of the left frontal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Beta waves appear when performing high degree cognitive functions such as during normal waking and concentration. Puzzle tasks, a medum which is frequently used as auxiliary materials for learning, require judgement of spatial relationships and logical thinking 20 , 21 , 22 ) , and research has shown that the frontal area is more activated 10 ) during puzzle performance. During puzzle task performance in this study there was activation of the left frontal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…In the built environment, gamification has been of particular interest to researchers specialising in the different facets of architectural computing, often with emphasis on collaborative and participatory activities: Aydin et al (2014) employed it in the context of shape grammars for mass-housing design, while more recently Savov et al (2016) employed it for facade design. Its importance for educating both specialised users and laypeople has also been of interest: Bertuzzi and Zreik (2011) applied mixedreality games to raise awareness of cultural heritage issues; Chang (2004) employed design puzzles to support design learning; and later on Liang and Chang (2006) expanded the concept with the DiGame design game. In the more specialised field of environmental design, sustainable energy use has been a focus, as described by Gustafsson et al (2009) and Cohen et al (2013).…”
Section: The Role Of Game Playingmentioning
confidence: 99%
“…If this were taken literally, some insights might be achieved in untangling the puzzle-making and puzzlesolving procedures underpinning the design process. Chang (2004) attempts this and generates a design puzzle that starts with an abstract model of mapping the features of puzzle games onto the design process [2]. It argues that designing has a marked similarity with puzzle games with its puzzlemaking and puzzle-solving process.…”
Section: Design Puzzles As Model Of Design For Linking Ideasmentioning
confidence: 99%
“…The design puzzle shows that solving puzzles require some knowledge of the puzzle itself.The constructive hints and rule of the puzzles are important factors for solving them. Chang has categorized the elements of the design puzzle into 'hint', 'puzzle rules' and 'puzzle goal', and this categorization provide a way of describing teaching capability through an emphasis on methods of learning through puzzles [2]. (Figure 1).…”
Section: Design Puzzles As Model Of Design For Linking Ideasmentioning
confidence: 99%
See 1 more Smart Citation